2016
DOI: 10.7863/ultra.16.01052
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Characteristics of the Normal Achilles Tendon Assessed by Virtual Touch Imaging Quantification Shear Wave Elastography

Abstract: he Achilles tendon is the largest, thickest, and strongest tendon in the human body. Problems with the Achilles tendon are frequent in athletes and the general population because of the increased incidence of sports-related injuries, which cause foot and ankle pain. [1][2][3][4] The area 5 cm proximal to the calcaneus is especially predisposed to tendinopathy and subsequent tearing due to vascular and biomechanical factors. Sonography plays an important role in the evaluation of tendon disorders, owing to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 25 publications
5
38
1
Order By: Relevance
“…As a result, guided wave propagation may lead to a false evaluation of the Young modulus, which is the reason that shear wave velocities are usually preferred to Young moduli in tendon imaging [6,22,32]. In addition, the high shear wave velocity of hard tendon can exceed the upper limit of measurement of shear wave velocity of the device (maximum scale value) [32,33]. In the Acuson S3000 ultrasound system Virtual Touch imaging quantification (VTIQ; Siemens Medical Solutions, Malvern, PA, USA), the maximum scale value is 10 m/sec [33], and in the Imagine Aixplorer system (Supersonic Imagine, Aix-en-Provence, France), it is 16.3 m/sec [34].…”
Section: Clinical Applications Of Shear Wave Us Elastography To Tendomentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, guided wave propagation may lead to a false evaluation of the Young modulus, which is the reason that shear wave velocities are usually preferred to Young moduli in tendon imaging [6,22,32]. In addition, the high shear wave velocity of hard tendon can exceed the upper limit of measurement of shear wave velocity of the device (maximum scale value) [32,33]. In the Acuson S3000 ultrasound system Virtual Touch imaging quantification (VTIQ; Siemens Medical Solutions, Malvern, PA, USA), the maximum scale value is 10 m/sec [33], and in the Imagine Aixplorer system (Supersonic Imagine, Aix-en-Provence, France), it is 16.3 m/sec [34].…”
Section: Clinical Applications Of Shear Wave Us Elastography To Tendomentioning
confidence: 99%
“…Due to the high anisotropy, tendon imaging requires the US beam position to be perfectly parallel or perpendicular to the tendon fibers; however, the tendons may have a complex structure due to interpenetration and rotation of fibers from muscles, and sometimes proper positioning of the US beam cannot be achieved [32,33]. Several studies of the Achilles tendon have reported large differences in elasticity values in the transverse (axial) and longitudinal (sagittal) orientations of the probe and the neutral position, extension, and dorsiflexion of the ankle [32,33,35,36].…”
Section: Clinical Applications Of Shear Wave Us Elastography To Tendomentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Arda et al 13 reported on elasticity values of Achilles tendons using a numeric scale in healthy volunteers, with a mean of 51.5 ± 25.1 kPa as Young modulus. During aging, Achilles tendon exhibited an increased stiffness when compared to young adults 14,15 ; however, other Authors did not find any correlation 16 . A positive correlation was found between tendon stiffness and BMI 17 ; results in smokers are controversial 17,18 .…”
Section: Normal Achilles Tendonmentioning
confidence: 77%
“…SE was also able to detect tissue changes in symptomatic patients with normal US 31 , and to screen athletes at risk of developing symptoms during the season 21 . For these reasons, SE is considered a valuable tool to valuate "in vivo" and in a non-invasive way the biomechanical properties of various tendons 16 bypassing artefacts of surgical repair, such as tendons sutures 38 .…”
Section: Discussionmentioning
confidence: 99%